PENGARUH PEMBERIAN HORMON 2,4-D DAN BAP TERHADAP PERTUMBUHAN KALUS JERUK KASTURI (Citrus microcarpa) SEBAGAI PENGEMBANGAN HANDOUT PADA KONSEP BIOTEKNOLOGI MODERN DI SMA - Sari, Yeni; Mahadi, Imam; Syafi’i, Wan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The aims of this research to determine the effect of the hormone 2,4-D and BAP on callus growth Kasturi Orange (Citrus microcarpa) and designing relevant teaching materials on the concept of Modern Biotechnology tissue culture for high school students. This research consisted of two phases. The first phase of that research using experimental method completely randomized design factorial. Parameters observed is percentage of explants, while appearing callus, callus width and texture of the callus. Research results and a growing percentage of the width callus explants were analyzed by ANOVA and a further test DMRT at 5% level, when it appears callus and callus texture done by descriptively. Phase II this research is a handout development stages of learning that comes from the results on the first phase research using ADDIE development model (Analyze, Design, Development, Implementation, and Evaluation) simplified to the stage Analyze,Design, and Developmet and then will validation with 5 category. The result shows that a combination of hormones D4B1 and D4B2 produces a callus emerged fastest of 3.3 HSK. The highest percentage of callus formation that is 100% contained in the treatment of D2B0, D2B0.5 - D4B0. The mean width of callus was highest in treatment D4B2 with a width of 0.97cm. Embryogenic callus resulting by treatment of D2B1, D2B2 ,and D3B0. The results of reseach can be used as teaching material in the form of handouts of Biology subjects at the concept of Modern Biotechnology in high school with value of 4 categories validity valid.   Keywords: Hormones, Callus, Orange Kasturi, Handout,